2023
DOI: 10.1136/bmjopen-2022-061945
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of burnout and mental health problems among medical staff during the COVID-19 pandemic: a systematic review and meta-analysis

Abstract: ObjectiveThe COVID-19 pandemic has had a significant impact on the burnout and mental health of medical staff. This meta-analysis aims to provide additional (and updated) evidence related to burnout and mental health problems among medical staff using a broader data pool.DesignSystematic review and meta-analysis.Data sourcesPubMed, Embase, Cochrane Library, CNKI, Wanfang data and three preprint databases (SSRN, bioRxiv and medRxiv) were searched from 1 January 2020 to 17 May 2021.Eligibility criteriaWe include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 77 publications
0
9
2
Order By: Relevance
“…Although the prevalence of work impairment depends on the category of occupation and other factors, such as workers' comorbidities, it was generally in the range of 20–40% in studies reported before the COVID‐19 pandemic, 21,27,28 which is consistent with the prevalence of 24.8% in the present study. Regarding psychological distress, the prevalence reported in this study, 15.2%, appears to be lower than that reported in previous studies carried out during the COVID‐19 pandemic, although a direct comparison is difficult because of the differences in the study design, target population and assessment methods 1–3 . The analytic sample in the present study was limited to doctors; however, doctors might be less susceptible to psychological distress than other healthcare workers 29–31 .…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…Although the prevalence of work impairment depends on the category of occupation and other factors, such as workers' comorbidities, it was generally in the range of 20–40% in studies reported before the COVID‐19 pandemic, 21,27,28 which is consistent with the prevalence of 24.8% in the present study. Regarding psychological distress, the prevalence reported in this study, 15.2%, appears to be lower than that reported in previous studies carried out during the COVID‐19 pandemic, although a direct comparison is difficult because of the differences in the study design, target population and assessment methods 1–3 . The analytic sample in the present study was limited to doctors; however, doctors might be less susceptible to psychological distress than other healthcare workers 29–31 .…”
Section: Discussioncontrasting
confidence: 68%
“…[29][30][31] In addition, the doctors in this study were not necessarily involved in the direct care of COVID-19 patients; this might have made the prevalence of psychological distress lower, because directly engaging in COVID-19 care has been associated with a higher prevalence of depression among healthcare workers. 3 Considering that the prevalence of work impairment and psychological distress observed in this study were not particularly high compared with those reported in other studies, it is possible that the mental health status of geriatricians in Japan might not have worsened during the COVID-19 pandemic. However, as no studies have been carried out on geriatricians before the pandemic, future studies are needed to evaluate the longitudinal changes in psychological distress and work impairment in this population.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations